Penyelenggaraan Program Keaksaraan Dasar Terintegrasi Vokasional Skill Di Desa Tukamasea Kecamatan Bantimurung Kabupaten Maros - Fatmawati Gaffar; Rudi Amir; Kartini Marzuki (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Implementation of the Vocational Skills Integrated Basic Literacy Program, consisting of: 1) Strategies for integrating vocational skills in the basic literacy program  ; 2) Factors affecting the implementation of basic literacy program learning.  Thestrategies applied in the integration  of vocational skills in thebasic literacy program are: a) Determinationof program progress; b) Identification; c) Implementation of learning; d) Learning outcomes. Meanwhile, the factors supporting the implementation of basic literacy in mastering the literacy of residents studying in Tukamasea Village, Bantimurung District, Maros Regency, include: 1) Indonesian Bugis-Makassar dialect as the native mother tongue used as the main communication of learning residents, 2) The quality of literacy tutors, 3) Positive responses of learning residents to basic literacy programs, 4) Motives of residents to learn and family support,  10) Community support for the program, as well as 5) Good coordination ability between parties related to program implementation.